2021
DOI: 10.3127/ajis.v25i0.2845
|View full text |Cite
|
Sign up to set email alerts
|

Intelligent agent based framework to augment warehouse management systems for dynamic demand environments

Abstract: Warehouses are being impacted by increasing e-commerce and omni-channel commerce. The design of current WMSs (Warehouse Management Systems) may not be suitable to this mode of operation. The golden rule of material handling is smooth product flow, but there are day-to-day operational issues that occur in the warehouse that can impact this and order fulfilment, resulting in disruptions. Standard operational process is paramount to warehouse operational control but may preclude a dynamic response to real-time op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…In the publication by Binos et al [93], an intelligent agent-based framework is introduced to enhance warehouse management systems (WMS) in dynamic demand environments. The authors provide a novel framework that offers a triple contribution, encompassing innovative design principles and approaches for efficient WMS implementation.…”
Section: Miscellaneousmentioning
confidence: 99%
“…In the publication by Binos et al [93], an intelligent agent-based framework is introduced to enhance warehouse management systems (WMS) in dynamic demand environments. The authors provide a novel framework that offers a triple contribution, encompassing innovative design principles and approaches for efficient WMS implementation.…”
Section: Miscellaneousmentioning
confidence: 99%
“…Pulungan et al (2013) proposed an intelligent WMS (i-WMS), which comprises five subsystems, and the design integrates advanced intelligent system applications such as neural network, fuzzy control, bee colony optimization. And a decision support system and technologies such as RFID and Androidbased handheld devices (Binos et al, 2021, Pulungan et al, 2013. Minbo et al (2011) suggested RFID-based Intelligent WMS (RFID-IWMS), addressing critical limitations of the traditional bar-code base system, such as lack of integration with the WMS and difficulty to get Key Performance Indicator (KPI) data of the operation.…”
Section: Advanced Features Of Extended Warehouse Management Systems (...mentioning
confidence: 99%
“…Analyzing the technologies that led to the development of Warehousing, it is worth paying attention to the evolution of Warehouse Management Systems (WMS), as one of the most important components on the basis of which the requirements for warehouse automation in Smart Manufacturing are implemented and achieved [28][29][30][31][32]. Based on the analysis, the following technologies were selected as the basis for each stage of WMS development, which are presented in table 2 for ease of comparison.…”
Section: Fig 2 Evolution Of Warehousingmentioning
confidence: 99%